The Chaperonin GroEL: A Versatile Tool for Applied Biotechnology Platforms - O'Neil, Pierce T.; Machen, Alexandra J.; Deatherage, Benjamin C.; Trecazzi, Caleb; Tischer, Alexander; Machha, Venkata R.; Auton, Matthew T.; Baldwin, Michael R.; White, Tommi A.; Fisher, Mark T. (Frontiers in Molecular Biosciences, 2018)
The nucleotide-free chaperonin GroEL is capable of capturing transient unfolded or partially unfolded states that flicker in and out of existence due to large-scale protein dynamic vibrational modes. In this work, three short vignettes are presented to highlight our continuing advances in the application of GroEL biosensor biolayer interferometry (BLI) technologies and highlights expanded uses of GroEL as a molecular scaffold for electron microscopy determination. The first example presents an extension of the ability to detect dynamic pre-aggregate transients in therapeutic protein solutions where the assessment of the kinetic stability of any folded protein or, as shown herein, quantitative detection of mutant-type protein when mixed with wild-type native counterparts. Secondly, using a BLI denaturation pulse assay with GroEL, the comparison of kinetically controlled denaturation isotherms of various von Willebrand factor (vWF) triple A domain mutant-types is shown. These mutant-types are single point mutations that locally disorder the A1 platelet binding domain resulting in one gain of function and one loss of function phenotype. Clear, separate, and reproducible kinetic deviations in the mutant-type isotherms exist when compared with the wild-type curve. Finally, expanding on previous electron microscopy (EM) advances using GroEL as both a protein scaffold surface and a release platform, examples are presented where GroEL-protein complexes can be imaged using electron microscopy tilt series and the low-resolution structures of aggregation-prone proteins that have interacted with GroEL. The ability of GroEL to bind hydrophobic regions and transient partially folded states allows one to employ this unique molecular chaperone both as a versatile structural scaffold and as a sensor of a protein’s folded states.